Identification of characteristics for RC Low Pass, High Pass, Band Pass and Band Stop Filters - Maung Aye; Tin Tin Hla (The Indonesian Journal of Computer Science, 2025)
In signal processing, filters are essential components used to modify the frequency content of signals, enabling the separation of desired components from unwanted noise or interference. Among the most commonly used filters in electronic systems are RC (Resistor-Capacitor) filters, which include low-pass, high-pass, band-pass, and band-stop filters. These filters are simple to implement and widely utilized for tasks such as noise reduction, signal shaping, and frequency selection. The performance of these filters varies significantly with desired frequency, and understanding these variations is crucial for their optimal application. The designed parameters and values are calculated and the gain magnitude and phase response and bode response is simulated with MATLAB.